Availability of exchangeable potassium due to cocoa pods husk and coffee wastes amended with urea and impact on some other soil physico-chemical properties in a ferralsol of west Cameroon - Mboua, Etienne; Bitondo, Dieudonne; Tabi, Fritz Oben; Boukong, Alexis (Current Research in Agricultural Sciences, 2023)
This incubation trial was carried out to determine the effect of urea amendment of cocoa pods husk (CP) and coffee wastes (CW) on their ability to improve some physico-chemical properties and potassium availability in a Ferralsol of the Western region of Cameroon. It was conducted using a completely randomized design consisting of seven treatments and three replications. Modalities included three doses of urea (0; 0.003 and 0.006g per 100g of dry soil corresponding to 0, 75 and 150 Kg per hectare) combined with 0.225 g corresponding to 5 t.ha-1 for each organic residue in addition to the control. The study was conducted under aerobic conditions, at a temperature of 28°C and in darkness for 90 days. The Changes in the studied parameters was taking every 30 days. Compared to the control, the urea amendment of the bio-waste studied reduced the alkalinity and the negative net charge of the soil. On the other hand, it improved organic carbon mineralization and potassium availability (0.81 cmol+/kg with 5 t.ha-1 of CP + 75 to 150 kg.ha-1 of urea compared to 0.48 cmol+/kg for the control). Urea amendment of cocoa pods husk and coffee wastes can therefore improve the availability of potassium and the mineralisation of organic carbon from these residues in ferralsols.